Exploring the Intranasal Medication Delivery Methods for the Management of Hypertension (Asian Journal of Pharmaceutics (AJP), 2024)
Intranasal drug delivery systems (INDS) have attracted interest as a possible tactic to enhance the bioavailabilityand absorption of medications. The use of INDS to treat hypertension (HTN), a prevalent cardiovascular ailment,is examined in this review study. The paper describes the ability for medication to cross the nasal barrier and givesa summary of the cellular and structural makeup of the nasal cavity. It talks about many options and strategies toimprove the way nasal drugs are delivered, with an emphasis on devices that make use of nanotechnology. Thepaper also includes a thorough analysis of the various approaches to treating HTN and a discussion of how INDScan enhance medication efficacy and lessen systemic side effects. This review compiles available literature onformulation strategies, relevant in vivo, ex vivo, and in vitro assessment technologies, as well as the advancementof studies concerning the role of the nasal epithelium in the systemic circulation of antihypertensive medications.With intranasal delivery, the first-pass impact is removed, doses are lowered, and drug bioavailability is enhanced.Future research in this area may lead to more effective and patient-friendly HTN therapies.